The pectoral fin muscles of the coelacanth Latimeria chalumnae: Functional and evolutionary implications for the fin‐to‐limb transition and subsequent evolution of tetrapods. Issue 9 (22nd July 2016) - Miyake, Tsutomu; Kumamoto, Minayori; Iwata, Masamitsu; Sato, Ryuichi; Okabe, Masataka; Koie, Hiroshi; Kumai, Nori; Fujii, Kenichi; Matsuzaki, Koji; Nakamura, Chiho; Yamauchi, Shinya; Yoshida, Kosuke; et al.
ABSTRACT: To investigate the morphology and evolutionary origin of muscles in vertebrate limbs, we conducted anatomical dissections, computed tomography and kinematic analyses on the pectoral fin of the African coelacanth, Latimeria chalumnae . We discovered nine antagonistic pairs of pronators and supinators that are anatomically and functionally distinct from the abductor and adductor superficiales and profundi. In particular, the first pronator and supinator pair represents mono‐ and biarticular muscles; a portion of the muscle fibers is attached to ridges on the humerus and is separated into two monoarticular muscles, whereas, as a biarticular muscle, the main body is inserted into the radius by crossing two joints from the shoulder girdle. This pair, consisting of a pronator and supinator, constitutes a muscle arrangement equivalent to two human antagonistic pairs of monoarticular muscles and one antagonistic pair of biarticular muscles in the stylopod between the shoulder and elbow joints. Our recent kinesiological and biomechanical engineering studies on human limbs have demonstrated that two antagonistic pairs of monoarticular muscles and one antagonistic pair of biarticular muscles in the stylopod (1) coordinately control output force and force direction at the wrist and ankle and (2) achieve a contact task to carry out weight‐bearing motion and maintain stable posture. Therefore, along with dissections of the pectoral fins in two lungfish species, Neoceratodus forsteri and Protopterus aethiopicus, we discuss the functional and evolutionary implications for the fin‐to‐limb transition and subsequent evolution of tetrapods. Anat Rec, 299:1203–1223, 2016. © 2016 Wiley Periodicals, Inc.